The influence of social determinants on sexual risk among out-of-school African American female adolescents - Browne, Felicia A. (Vulnerable Child Youth Stud, 2013)
Formative research was conducted to understand the social determinants of HIV risk among African American female adolescents as part of a systematic adaptation of an evidence-based behavioral HIV prevention intervention, the Women’s CoOp. Semi-structured in-depth interviews were conducted between November 2008 and April 2009 with 20 African American female adolescents aged 16–18 who reported engaging in sex, using alcohol or other drugs, and dropping out of school. All interviews were audio recorded, transcribed, and coded for key themes and emergent content patterns. The findings indicate that while female adolescents are knowledgeable about HIV and other sexually transmitted infections (STIs), myriad social factors relate to their level of risk. Interpersonal relationships, primarily with older boyfriends and friends, played a pivotal role in their decision-making regarding sex risk behavior, substance use, and educational attainment. A lack of viable employment opportunities, exacerbated by the lack of a high school education, resulted in some young women trading sex to make money. In addition, violence, victimization, and gang involvement are pervasive in their communities. Out-of-school African American female adolescents face a plethora of issues that are directly and indirectly related to their sex risk behaviors and consequently their HIV/STI risk. To reach a vulnerable population disproportionately affected by HIV and other STIs, these factors must be addressed in prevention interventions, when feasible. The findings were incorporated into the intervention adaptation that is currently being tested in a randomized controlled trial.